The Effectiveness of Team Pair Solo Technique in Teaching Speaking:: An Experimental Study at the First Semester of Madrasah Ibtidaiyah Teacher Training Program in the Academic Year of 2024/2025 - Rahmawati, Widya; Permana, Rian Sigit Gesang (Indonesian Research Journal on Education, 2024)
Team Pair Solo (TPS) is a method of cooperative learning in which the students do problem first as a team, then with a partner, and finally on their own. It is designed to motivate the students to tackle and succeed at problem which initially were beyond their ability. And then all students take individual quizzes on the material. The purpose in this research is to answer and investigate the effect of Team Pair Solo technique in teaching speaking related to speaking skill. In this research, quasi-experimental design used pre-test and post-test design. The writers given the test of two classes as subject, so there were control class and experimental class as compared. Despite this, the writers used quantitative approaches because the analyzed data was homogeny. The result of homogeneity test is to know the equivalent in capability before the writers give the treatment to the experimental group. Based on the research finding, it is found that the statistic computation from the post-test support the hypothesis and the students taught by using Team Pair Solo technique have better scores in speaking than those taught by using non-Team Pair Solo. This finding means that the alternative hypothesis is accepted. It is proved from the computation where computed F-value (23.196) was higher than the critical F-value (4.098) in significant level 0.05. The t-value shows 4.816, the sig. shows 0.000. The significance level is lower than 0.05 (0.000<0.050). Therefore, it can be concluded that Think Pair Solo technique is effective in teaching speaking.